Wage-Setting Institutions as Industrial Policy - Magnus Henrekson; Steven J. Davis (The Research Institute of Industrial Economics (IUI), 2000)
Centralized wage-setting institutions compress relative wages. Motivated by this fact, we investigate the effects of centralized wage setting on the industry distribution of employment. We examine Sweden's industry distribution from 1960 to 1994 and compare it to the U.S. distribution over the same period. We relate U.S.-Swedish differences in the industry distribution and their evolution over time to the structure of relative wages between and within industries. The empirical results identify the rise and fall of centralized wage-setting arrangements as a major factor in the evolution of Sweden's industry distribution. The compression associated with centralized wage-setting shifted the industry distribution of Swedish employment in three respects: away from industries with high wage dispersion among workers, away from industries with a high mean wage, and, most powerfully, away from industries with a low mean wage. By the middle 1980s, these wage structure effects accounted for about 40 percent of U.S.-Swedish differences in the industry distribution. The dissolution of Sweden's centralized wage-setting arrangements beginning in 1983 led to widening wage differentials and a reversal in the evolution of U.S.-Swedish differences in industry structure.
Keywords: J23; J51; L50; P52; 330; Industry distribution of employment; Labor market institutions; Labor market policy; Wage dispersion; Wage-setting institutions; Tarifverhandlungen; Beschäftigungsstruktur; Lohnstruktur; Vergleich; Schweden; USA